Evaluation of Clipping and Filtering-Based PAPR Reduction in OFDM System - Wirastuti, N. M. A. E. D.; Pramaita, N.; Suyadnya, I M. A.; Khrisne, D. C. (Journal of Electrical, Electronics and Informatics, 2017)
This paper investigates clipping and filtering techniques in reducing peak average power ratio (PAPR) of Orthogonal Frequency Division Multiplexing (OFDM) system. The concept of OFDM is to split a high speed serial data into parallel data at a lower speed, then the parallel data carried by mutually orthogonal subcarriers. The high of PAPR is one of disadvantages of OFDM system. The high PAPR can damages the form of OFDM and reduces its performance. The purpose of this study is to reduce PAPR using simulation. OFDM was simulated with and without clipping filtering then compared.  The methods used to reduce PAPR was clipping and filtering technique. Clipping and filtering technique operates by clipping the output of inverse Fourier transform that exceed the threshold. Graphics PAPR vs. CCDF was used to evaluate the performance of OFDM systems. PAPR for OFDM system using Fourier transform when CCDF = 10 -3 is 11,2 dB, with classical clipping PAPR was 4,1 dB and PAPR 4,6 dB when with deep clipping.